Kajian Keamanan Penggunaan Daun Binahong (Anredera cordifolia (Ten.) Stennis) sebagai Kandidat Imbuhan Pakan dalam Rumen In Vitro: Study of Anredera cordifolia (Ten.) Stennis Leaves Safety as a Candidate Feed Additive in In Vitro Rumen - Evvyernie, Dwierra; Zahera, Rika; Husna, Hafidzatul; Toharmat, Toto (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
This study evaluated the safety of binahong leaves (Anredera cordifolia (Ten.) Stennis) as a potential rumen feed additive through microbiological observations and in vitro fermentation characteristics. Microbiological testing used binahong leaf infusion extract with levels of 0%, 5%, 10%, 15%, and 20%, then measured total bacterial and protozoal populations. In vitro experiment used a Randomized Block Design with seven ration treatments and three groups of rumen fluid collection times, with control ration (60% Forage: 40% Concentrate), and suplementation binahong leaf 2.5%, 5%, 7.5%, 10%, 12.5%, and 15%. In vitro parameters include fermentability (total N–NH₃ and VFA, microbial protein synthesis, and digestibility (dry matter and organic matter). Data were analyzed using analysis of variance followed by orthogonal polynomial tests. The results showed that binahong leaf infusion extract up to 20% caused a linear reduction in total bacterial and protozoal populations but remained within normal ranges. The use of binahong leaf powder (TSB) in the ration of more than 7.5% resulted in a decrease in all in vitro variables to abnormal levels. In conclusion, binahong leaves are safe for rumen microbial activity when applied as an infusion extract up to 20%, whereas their use as leaf powder in dairy cattle rations should be limited to 7.5% to maintain normal fermentation, microbial protein synthesis, and in vitro digestibility.